2017
DOI: 10.3390/w9020104
|View full text |Cite
|
Sign up to set email alerts
|

A Percolation‐Based Approach to Scaling Infiltration and Evapotranspiration

Abstract: Abstract:Optimal flow paths obtained from percolation theory provide a powerful tool that can be used to characterize properties associated with flow such as soil hydraulic conductivity, as well as other properties influenced by flow connectivity and topology. A recently proposed scaling theory for vegetation growth appeals to the tortuosity of optimal paths from percolation theory to define the spatio-temporal scaling of the root radial extent (or, equivalently, plant height). Root radial extent measures the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 51 publications
(110 reference statements)
0
6
0
Order By: Relevance
“…However, in [80] it was shown that the length and time scales of the mean growing season transpiration, T g , and growing season length, t g , can be used in the scaling relationship for RRE = T g (t/t g ) 1/1.21 . More importantly, since the yearly increase in RRE turns out to equal the transpiration [80], the root volume, which increases as the RRE to the mass fractal dimension, Guidance for the choice of d f was taken from percolation theory and general knowledge about the architecture of roots and the soil (see Figure 2 for details). It has often been noted that the bulk of root mass is found in the top 2 m of soil [72], or the top 1 m [73].…”
Section: Concepts From Percolation Theorymentioning
confidence: 99%
“…However, in [80] it was shown that the length and time scales of the mean growing season transpiration, T g , and growing season length, t g , can be used in the scaling relationship for RRE = T g (t/t g ) 1/1.21 . More importantly, since the yearly increase in RRE turns out to equal the transpiration [80], the root volume, which increases as the RRE to the mass fractal dimension, Guidance for the choice of d f was taken from percolation theory and general knowledge about the architecture of roots and the soil (see Figure 2 for details). It has often been noted that the bulk of root mass is found in the top 2 m of soil [72], or the top 1 m [73].…”
Section: Concepts From Percolation Theorymentioning
confidence: 99%
“…Thus the height prediction generated by using the maximum flow velocity of 1 μm s −1 and a length scale of 10 μm is coincident with the height prediction using T g = 1650 mm and t g = 180 d, where 1650 mm is the largest transpiration value recorded in a world biome survey (Box et al, 1989) and 180 d is a characteristic growing season. More importantly, perhaps, the lower limit pore‐scale fluid flow velocity proposed here with the same length scale of 10 μm generates the lower limit plant height curve (Hunt et al, 2017) with the smallest transpiration observed, in the Namibian desert (Seeley, 1978), of 20 mm. Note that Eq.…”
Section: Theorymentioning
confidence: 66%
“…Hunt et al (2017), who addresses the upscaling of transpiration, showed that Eq. [1] for plant growth could be equally represented as H=Tnormalg(ttnormalg)1/1.217 where H is the plant height (or RRE), T g is the transpiration in a growing season, and t g is the length of the growing season.…”
Section: Theorymentioning
confidence: 99%
“…This two-term formulation enjoys a rigorous mathematicalphysical underpinning. This includes recent work of Hunt et al (2017), who used percolation theory to interpret S and 𝑐𝐾 s . The use of 𝑑 = 2 expansion terms, however, has an important side effect.…”
Section: Core Ideasmentioning
confidence: 99%